Identifikasi Papasan (Coccinia grandis (L.) Voigt) di Tiga Populasi di Yogyakarta - Rindyastuti, Ridesti; Daryono, Budi Setiadi (JURNAL BIOLOGI INDONESIA, 2009)
ABSTRACTSpecies Identification of Scarlet gourd (Coccinia grandis (L.) Voigt) in Three Population inYogyakarta. Papasan is a dioecious plant belongs to the family Cucurbitaceae. This plant iscommonly used as vegetable, anti diabetic, anti bacterial, and anti diarrhea. In Daerah IstimewaYogyakarta, there were two varians of Papasan (Papasan I and II), found in three population(Ngebel, Berbah and Gajah Wong Riverbank). They differ in phenotype, especially in shapeand taste of fruit. Genotype observation using squash method on the root tips with modificationin the duration of maceration were used in this research indicated that cells devided of PapasanI at about 8-11.30 a.m, while Papasan II at about 08.30-09.30 a.m, 11 a.m-00.30 p.m and 2-2.30p.m. The chromosome number of both Papasan is 2n=24, contains of 22 autosomes and 2 sexchromosomes. The karyotype formulas of Papasan I and II were 2n=24=20m+2sm+XX(m).Based on the statistic test, significant difference on chromosomes character between PapasanI and II was only in short arm of autosome pair number 5. The difference R value betweenPapasan I and II was smaller than 0.25. It revealed that the both of Papasan is closely relatedand belongs to the same species of Coccinia grandis L. Character differences between bothof Papasan only revealed physiology adaptation.Keywords: Coccinia grandis L., Papasan, Chromosome, Karyotype.Kata kunci: Coccinia grandis L., Papasan., Cromosom, Kariotype.